Política curricular e relações raciais: a Lei 10.639/2003 nos discursos de documentos oficiais da educação básica e ensino superior na Amazônia Bragantina-Pa - GUIMARÃES, Deidiane Costa (2021)
This study aims to analyze the discourses of official documents about the implementation of Law No. 10.639 / 2003 in the curriculum of Basic Education and Higher Education, from the executing agencies SEDUC, SEMED, UFPA and supervisors (Pará State Board of Education and Bragança State Council). The research is qualitative approach. The methodological procedure used in the study was the documentary analysis of the State and Municipal Education Plan, Resolutions of the Pará State Board of Education and Bragança Municipal Board of Education and the Pedagogical Project of the UFPA Degree Course. Data were analyzed based on discourse analysis based on Bakhtin's discursive dialogism and specialized literature on the subject. The results reveal actions on the continuing education of education professionals, valorization of Afro-Brazilian and African culture, affirmative policies, didactic materials on the theme, regarding the implementation of Law No. 10.639 / 2003, regarding the State Education Plan, Municipal Plan of Education, Legislation of the State and Municipal Council of Education, and Curriculum Projects of Degree Courses of the Federal University of Pará. In addition, we emphasize the broadening of the discussion on Law 10.639 / 2003 in order to contribute to the construction of a democratic and anti-racist education that respects, recognizes and values the singularities and differences of each socio-cultural group, especially about Afro-Brazilian and African culture concerning educational and social contexts. We conclude on the implementation of Law No. 10,639 / 2003 through the actions evidenced in the documents dealing with Basic and Higher Education in the municipality of Bragança-PA, with important measures and strategies to build a multicultural curriculum, valuing cultural diversity, specifically about the valorization of black culture.